2022
DOI: 10.3389/fonc.2022.920287
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of DUB Enzyme in Hepatocellular Carcinoma

Abstract: According to GLOBOCAN 2021 cancer incidence and mortality statistics compiled by the International Agency for Research on Cancer, hepatocellular carcinoma (HCC) is the most common malignancy in the human liver and one of the leading causes of cancer death worldwide. Although there have been great advances in the treatment of HCC, such as regofenib, sorafenib, and lomvatinib, which have been developed and approved for the clinical treatment of advanced or metastatic HCC. However, they only prolong survival by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 202 publications
0
7
0
Order By: Relevance
“…Indeed, liver cancers, along with pancreatic cancer, generally have low survival rates ( 37 ). Ubiquitin dysregulation, due to imbalances between ubiquitinase and de-ubiquitinase activities, is thought to affect tumor development ( 38 40 ), but UCH de-ubiquitinases have been rarely studied in HCC, by contrast with USP enzymes ( 41 ). Only UCH37 has been investigated in liver cancer cells ( 42 ), but other family members may also have an impact.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, liver cancers, along with pancreatic cancer, generally have low survival rates ( 37 ). Ubiquitin dysregulation, due to imbalances between ubiquitinase and de-ubiquitinase activities, is thought to affect tumor development ( 38 40 ), but UCH de-ubiquitinases have been rarely studied in HCC, by contrast with USP enzymes ( 41 ). Only UCH37 has been investigated in liver cancer cells ( 42 ), but other family members may also have an impact.…”
Section: Discussionmentioning
confidence: 99%
“…Deubiquitination has a crucial role in tumorigenesis and progression, including cell differentiation, proliferation, metabolism, immunological evasion, and drug resistance, according to accumulating evidence [14] . Dysregulation of deubiquitination is associated with poor prognosis in HCC [19] . Identifying relevant prognostic signatures and formulating immunotherapeutic approaches for HCC may be aided by a deeper comprehension of the roles of various deubiquitination patterns and the characterization of TME infiltration [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous DUBs have been shown to be substantially expressed in cancerous tissues, including pancreatic cancer, lung cancer, and liver cancer [16] , [17] , [18] , indicating that deubiquitination is more active in tumours and closely associated with tumour progression. By modulating oncogenic factors such as c-Myc and FoxM1, deubiquitination can promote carcinogenesis and provide novel therapeutic targets in HCC [19] . Multiple investigations have shown that deubiquitination is intimately associated with drug resistance in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of optimal treatment options, personalized therapy as well as rational multidisciplinary interventions are the directions of recent efforts. The pathogenesis of HCC is more complex, and a deep understanding of the molecular mechanisms underlying the pathogenesis of HCC can provide effective therapeutic strategies to improve the survival rate of patients with HCC 9 . Current studies have found that cell deaths are important for inflammatory diseases 10 .…”
Section: Introductionmentioning
confidence: 99%